Ultraviolet curing epoxy acrylic resin and preparation method and application thereof

The flame-retardant polyvinyl alcohol is prepared through chemical modification, combined with modified vanillic acid and bisphenol A epoxy resin and other raw materials, and the existing ultraviolet cured epoxy acrylic resin has solved the problems of high viscosity, dark color and insufficient flame retardant performance. Colorless, transparent, flame-retardant, low viscosity ultraviolet cured epoxy acrylic resin suitable for many fields has been prepared, achieving rapid curing and high-quality coatings.

CN119285905APending Publication Date: 2025-01-10STATE GRID ZHEJIANG ELECTRIC POWER CO LTD NINGBO POWER SUPPLY CO
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411332908.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

While maintaining the original physical and chemical properties, the existing ultraviolet cured epoxy acrylic resin has too high viscosity, darker color, and insufficient flame retardant properties, which limits its application in many fields.

Method used

Flame-retardant polyvinyl alcohol is prepared by chemical modification, increasing the hydroxyl reaction site of modified vanillic acid, combined with bisphenol A epoxy resin, modified vanillic acid, methacrylic acid and photoinitiator for combination, and colorless and transparent preparation is prepared , flame retardant, excellent mechanical properties, low viscosity and good water solubility of ultraviolet cured epoxy acrylic resin.

Benefits of technology

It has achieved ultraviolet curing epoxy acrylic resin with fast curing speed, low energy consumption, less environmental pollution and high coating quality. It is suitable for wood floor paint, plastic paint, template paint or paper varnish, and has excellent resistance Fuel performance and storage stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses ultraviolet curing epoxy acrylic resin, which is prepared from the following raw materials in parts by weight: 80 to 90 parts of bisphenol A epoxy resin, 20 to 30 parts of methacrylic acid, 20 to 30 parts of modified vanillic acid, 0.1 to 3 parts of trimethyl benzyl ammonium chloride, 0.01 to 1 part of polymerization inhibitor and 1 to 6 parts of photoinitiator, and the modified vanillic acid has higher copolymerization reaction activity; the invention also discloses a preparation method of the ultraviolet-cured epoxy acrylic resin. The ultraviolet curing epoxy acrylic resin provided by the invention is colorless and transparent, has good flame retardant property, low viscosity, good water solubility and excellent mechanical property, and can be widely applied to many fields such as woodware floor paint, plastic paint, template paint, paper gloss oil and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of polymer materials, and in particular relates to an ultraviolet light-cured epoxy acrylic resin and a preparation method and application thereof. Background Art

[0002] UV-curable epoxy acrylate resin is a new type of environmentally friendly resin, which is obtained by esterification reaction of epoxy resin and acrylic acid or methacrylic acid. Epoxy acrylate resin is currently the most widely used and largest-volume photocurable oligomer. It has the characteristics of fast curing, chemical corrosion resistance, good mechanical properties and transparency, and is widely used in coatings, structural materials, optical devices and other fields.

[0003] The patent with application number CN201410036012.X provides a special resin for water-based UV-curing coatings, including the following raw materials: epoxy acrylate, catalyst, inhibitor and hexahydrophthalic anhydride. The diluent dosage in the water-based UV-curing coating of the invention is as low as 20wt%, and the resin content is as high as 50wt%, which reduces the use of organic solvents and increases the resin content, which is more in line with today's environmental protection requirements; however, this method changes the chemical structure of the original epoxy acrylate resin, making the epoxy acrylate resin too brittle, which limits its application in many fields. The patent with application number CN201710382827.7 provides a UV-curable low-viscosity epoxy acrylic resin, including the following raw materials: epoxy resin, inhibitor, catalyst A organic ammonium compound, (meth) acrylic acid, catalyst B iron compound and / or chromium compound. The UV-curable low-viscosity epoxy acrylic resin of the invention reduces the viscosity while retaining the original physical and chemical properties of the epoxy acrylic resin, and also has the advantages of good wettability and low yellowing; but the selected catalyst B is a colored metal compound, which makes the product containing residual metal catalyst darker in color, limiting its application.

[0004] Therefore, it is necessary to develop a colorless and transparent UV-curable epoxy acrylic resin with good flame retardancy, low viscosity, good water solubility and excellent mechanical properties. Summary of the invention

[0005] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a UV-curable epoxy acrylic resin. Compared with the traditional process, the UV-curable epoxy acrylic resin provided by the present invention has a fast curing speed, low energy consumption, less environmental pollution, and high coating quality, and can meet its application requirements in wood floor paint, plastic paint, template coating or paper varnish. The present invention also provides a preparation method of the UV-curable epoxy acrylic resin.

[0006] The technical solution adopted by the present invention to achieve the above-mentioned purpose is: A UV-curable epoxy acrylic resin comprises the following raw materials in parts by weight: 80-90 parts of bisphenol A epoxy resin, 20-30 parts of methacrylic acid, 20-30 parts of modified vanillic acid, 0.1-3 parts of trimethylbenzyl ammonium chloride, 0.01-1 parts of inhibitor, and 1-6 parts of photoinitiator; the preparation method of the modified vanillic acid is as follows: Step S1, dissolving dicyandiamide, urea and polyvinyl alcohol in dimethylformamide at 100-140° C. in an inert atmosphere, adding phosphoric acid and mixing evenly, stirring for 1-3 hours to obtain a mixed solution, and purifying the mixed solution by ultrafiltration, precipitating and vacuum drying to obtain flame-retardant polyvinyl alcohol; Step S2, dissolving the flame-retardant polyvinyl alcohol obtained in step S1 in dimethyl sulfoxide at 120-140° C. with stirring, then adding vanillic acid and dibutyltin dilaurate, reacting for 12-16 hours to obtain a mixed solution, pouring the mixed solution into acetone for precipitation, washing the precipitate with acetone, then crushing, sieving, and vacuum drying to obtain modified vanillic acid.

[0007] The invention utilizes flame-retardant polyvinyl alcohol to modify vanillic acid, thereby increasing the hydroxyl reaction sites in the molecular structure of the modified vanillic acid. The hydroxyl groups can cause the epoxy groups of the bisphenol A epoxy resin to undergo a ring-opening reaction, thereby increasing the reaction efficiency of the bisphenol A epoxy resin and the modified vanillic acid.

[0008] Furthermore, the bisphenol A epoxy resin has an epoxy value of 0.48-0.54 eq / 100g and a molecular weight of 3000-5000.

[0009] Furthermore, the polymerization inhibitor is one or more of p-hydroxyanisole, hydroquinone, 2,5-dimethylresorcinol, 2,6-di-tert-butyl-p-cresol, and p-chloroanisole.

[0010] Furthermore, the photoinitiator is one or more of 2,4-dihydroxybenzophenone, benzophenone, 1-hydroxycyclohexyl phenyl ketone, and benzoin ethyl ether.

[0011] Furthermore, in step S1, the mass ratio of polyvinyl alcohol, dicyandiamide, urea and phosphoric acid is 6:4-6:8-10:5-8, and the amount of polyvinyl alcohol added to the dimethylformamide is 6-12 g / 100 mL.

[0012] Furthermore, in step S2, the mass ratio of the flame retardant polyvinyl alcohol, vanillic acid and dibutyltin dilaurate is 16:15-20:1-3, and the amount of the flame retardant polyvinyl alcohol added to the dimethyl sulfoxide is 8-16 g / 100 mL.

[0013] The invention also provides a method for preparing a UV-curable epoxy acrylic resin, comprising the following steps: adding bisphenol A epoxy resin, modified vanillic acid, trimethylbenzyl ammonium chloride, a polymerization inhibitor and a photoinitiator into a reactor equipped with a thermometer, a reflux condenser and a dropping funnel according to the component proportion under stirring conditions at 90-100° C., adding methacrylic acid dropwise after mixing evenly, and completing the dropping within 0.5-1.5 hours, heating to 100-110° C., keeping the temperature for 0.5-1.5 hours, measuring the acid value once every hour, and when the acid value drops to 4-5 mg KOH / (mg·g -1 ), stop the reaction, cool naturally to 60-70°C, discharge the material and store in the dark.

[0014] The above-mentioned UV-curable epoxy acrylic resin is used in wood floor paint, plastic paint, template coating or paper varnish.

[0015] The present invention has the following beneficial effects: The invention prepares modified vanillic acid by chemical modification. First, phosphoric acid is reacted with part of hydroxyl groups in a polyvinyl alcohol molecular chain to undergo an esterification reaction to obtain flame-retardant polyvinyl alcohol. The flame-retardant polyvinyl alcohol contains a phosphoric acid group in its structure. Under high temperature conditions, the thermal degradation products of the phosphoric acid group will cause the surface of the polymer to rapidly dehydrate and carbonize to form a carbonized layer. Since the carbonized layer cannot burn, it has a flame-retardant protective effect. In addition, the phosphoric acid group can decompose at the combustion temperature to generate a non-volatile glass-like substance, which can be wrapped on the polymer surface to form a dense protective layer to isolate oxygen and heat sources, thereby inhibiting combustion and further improving the flame-retardant properties of the polymer. Then, flame-retardant polyvinyl alcohol is used as a modifier to modify vanillic acid to obtain modified vanillic acid. The unique zigzag structure of polyvinyl alcohol makes it have excellent mechanical properties and is a polyhydroxy long-chain polymer. Vanillic acid is an organic acid containing a carboxyl group and a phenolic hydroxyl group on the benzene ring. Therefore, the flame-retardant polyvinyl alcohol can further undergo an esterification reaction with vanillic acid.

[0016] The invention uses flame-retardant polyvinyl alcohol to modify vanillic acid, increases the hydroxyl reaction sites in the molecular structure of the modified vanillic acid, and makes the modified vanillic acid have higher copolymerization reaction activity. Bisphenol A epoxy resin, modified vanillic acid, methacrylic acid, and a photoinitiator are compounded, and each raw material component can react with each other. The prepared ultraviolet light-cured epoxy acrylic resin has the advantages of being colorless and transparent, flame-retardant, having excellent mechanical properties, low viscosity, good water solubility, fast curing speed, and the like. DETAILED DESCRIPTION

[0017] The following will be combined with the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0018] The raw materials used in the following examples are all common commercial products. The epoxy value of bisphenol A epoxy resin is 0.48-0.54 eq / 100g, and the molecular weight is 3000-5000; the alcoholysis degree of polyvinyl alcohol is 85-89, and the molecular weight is 16000-20000.

[0019] Example 1 A UV-curable epoxy acrylic resin comprises the following raw materials in parts by weight: 80 parts of bisphenol A epoxy resin, 20 parts of methacrylic acid, 20 parts of modified vanillic acid, 0.1 parts of trimethylbenzyl ammonium chloride, 0.01 parts of inhibitor, and 1 part of photoinitiator; The inhibitor is p-hydroxyanisole and the photoinitiator is 2,4-dihydroxybenzophenone; The preparation method of modified vanillic acid is as follows: Step S1, at 100° C. and in a nitrogen atmosphere, 4 g of dicyandiamide, 8 g of urea, and 6 g of polyvinyl alcohol were dissolved in 100 mL of dimethylformamide, and 5 g of phosphoric acid was added and mixed evenly, and the mixture was stirred for reaction for 1 h to obtain a mixed solution, and the mixed solution was dissolved in 100 mL of deionized water, filtered with an ultrafiltration membrane (a ceramic ultrafiltration membrane with a pore size of 0.01-0.1 μm), and then added to 100 mL of a 6M hydrochloric acid aqueous solution, and ultrafiltration was performed again for purification, and finally the solution after ultrafiltration was poured into 50 mL of ethanol, stirred and mixed evenly, and allowed to stand for precipitation for 2 h, solid-liquid separation was performed to obtain a precipitate, and the precipitate was vacuum dried at 30° C. to constant weight to obtain a flame-retardant polyvinyl alcohol, and the grafting rate of the flame-retardant polyvinyl alcohol was 12.36%; Step S2, dissolving 16 g of flame-retardant polyvinyl alcohol obtained in step S1 in 50 mL of dimethyl sulfoxide at 120° C. with stirring, then adding 15 g of vanillic acid and 1 g of dibutyltin dilaurate, reacting for 12 h to obtain a mixed solution, pouring the mixed solution into 200 mL of acetone and precipitating for 2 h, crushing and sieving the precipitate to obtain a solid powder with a particle size of about 120 mesh, then washing with 100 mL of acetone, and finally drying in vacuo at 60° C. to constant weight to obtain modified vanillic acid.

[0020] A method for preparing ultraviolet light-cured epoxy acrylic resin comprises the following steps: adding bisphenol A epoxy resin, modified vanillic acid, trimethylbenzyl ammonium chloride, an inhibitor and a photoinitiator into a reactor equipped with a thermometer, a reflux condenser and a dropping funnel according to the component ratio at 90°C, adding methacrylic acid dropwise after mixing evenly, and completing the dropping within 0.5h, heating to 100°C, keeping the temperature for 0.5h, measuring the acid value every 1h, and measuring the acid value until the acid value drops to 4-5mg KOH / (mg·g -1 ), stop the reaction, cool naturally to 60-70°C, discharge the material and store in the dark.

[0021] Example 2 A UV-curable epoxy acrylic resin comprises the following raw materials in parts by weight: 90 parts of bisphenol A epoxy resin, 30 parts of methacrylic acid, 30 parts of modified vanillic acid, 3 parts of trimethylbenzyl ammonium chloride, 1 part of inhibitor, and 6 parts of photoinitiator; The inhibitor is 2,5-dimethylresorcinol and the photoinitiator is benzoin ethyl ether; The preparation method of modified vanillic acid is as follows: Step S1, dissolving 6g of dicyandiamide, 10g of urea, and 6g of polyvinyl alcohol in 50mL of dimethylformamide at 140°C in a nitrogen atmosphere, adding 8g of phosphoric acid and mixing evenly, stirring and reacting for 3h to obtain a mixed solution, dissolving the mixed solution in 100mL of deionized water, filtering with an ultrafiltration membrane (a ceramic ultrafiltration membrane with a pore size of 0.01-0.1 microns), and then adding it to 100mL of a 6M hydrochloric acid aqueous solution, ultrafiltration and purification again, finally pouring the ultrafiltration purified solution into 50mL of ethanol, stirring and mixing evenly, standing and precipitating for 2h, solid-liquid separation, obtaining a precipitate, and vacuum drying the precipitate at 30°C to constant weight to obtain a flame retardant polyvinyl alcohol, and the grafting rate of the flame retardant polyvinyl alcohol is 13.55%; Step S2, dissolving 16 g of flame-retardant polyvinyl alcohol obtained in step S1 in 100 mL of dimethyl sulfoxide at 140° C. with stirring, then adding 20 g of vanillic acid and 3 g of dibutyltin dilaurate, reacting for 6 h to obtain a mixed solution, pouring the mixed solution into 200 mL of acetone for precipitation for 2 h, crushing and sieving the precipitate to obtain a solid powder with a particle size of about 120 mesh, then washing with 100 mL of acetone, and finally drying in vacuo at 60° C. to constant weight to obtain modified vanillic acid.

[0022] A method for preparing ultraviolet light-cured epoxy acrylic resin comprises the following steps: adding bisphenol A epoxy resin, modified vanillic acid, trimethylbenzyl ammonium chloride, an inhibitor and a photoinitiator into a reactor equipped with a thermometer, a reflux condenser and a dropping funnel according to the component ratio at 100° C., adding methacrylic acid dropwise after mixing evenly, and completing the dropping within 1.5 hours, heating to 110° C., keeping the temperature for 1.5 hours, measuring the acid value every 1 hour, and measuring the acid value until the acid value drops to 4-5 mg KOH / (mg·g -1 ), stop the reaction, cool naturally to 60-70°C, discharge the material and store in the dark.

[0023] Example 3 A UV-curable epoxy acrylic resin comprises the following raw materials in parts by weight: 85 parts of bisphenol A epoxy resin, 25 parts of methacrylic acid, 25 parts of modified vanillic acid, 1 part of trimethylbenzyl ammonium chloride, 0.2 parts of inhibitor, and 3 parts of photoinitiator; The inhibitor is hydroquinone and the photoinitiator is benzophenone; The preparation method of modified vanillic acid is as follows: Step S1, dissolving 5g of dicyandiamide, 9g of urea and 6g of polyvinyl alcohol in 75mL of dimethylformamide at 130°C in a nitrogen atmosphere, adding 8g of phosphoric acid and mixing evenly, stirring and reacting for 2h to obtain a mixed solution, dissolving the mixed solution in 100mL of deionized water, filtering with an ultrafiltration membrane (a ceramic ultrafiltration membrane with a pore size of 0.01-0.1 microns), and then adding it to 100mL of a 6M hydrochloric acid aqueous solution, ultrafiltration and purification again, finally pouring the ultrafiltration purified solution into 50mL of ethanol, stirring and mixing evenly, standing and precipitating for 2h, solid-liquid separation, obtaining a precipitate, and vacuum drying the precipitate at 30°C to constant weight to obtain a flame retardant polyvinyl alcohol, and the grafting rate of the flame retardant polyvinyl alcohol is 13.02%; Step S2, dissolving 16 g of flame-retardant polyvinyl alcohol obtained in step S1 in 160 mL of dimethyl sulfoxide at 130° C. with stirring, then adding 18 g of vanillic acid and 2 g of dibutyltin dilaurate, reacting for 13 h to obtain a mixed solution, pouring the mixed solution into 200 mL of acetone and precipitating for 2 h, crushing and sieving the precipitate to obtain a solid powder with a particle size of about 120 mesh, then washing with 100 mL of acetone, and finally drying in vacuo at 60° C. to constant weight to obtain modified vanillic acid.

[0024] A method for preparing ultraviolet light-cured epoxy acrylic resin comprises the following steps: adding bisphenol A epoxy resin, modified vanillic acid, trimethylbenzyl ammonium chloride, an inhibitor and a photoinitiator into a reactor equipped with a thermometer, a reflux condenser and a dropping funnel according to the component ratio at 95°C, adding methacrylic acid dropwise after mixing evenly, and completing the dropping within 1 hour, heating to 105°C, keeping the temperature for 1 hour, measuring the acid value every 1 hour, and waiting for the acid value to drop to 4-5 mg KOH / (mg·g -1 ), stop the reaction, cool naturally to 60-70°C, discharge the material and store in the dark.

[0025] Comparative Example 1 A UV-curable epoxy acrylic resin comprises the following raw materials in parts by weight: 85 parts of bisphenol A epoxy resin, 20 parts of methacrylic acid, 25 parts of esterified modified vanillic acid, 1 part of trimethylbenzyl ammonium chloride, 0.2 parts of inhibitor, and 3 parts of photoinitiator; The epoxy value of bisphenol A epoxy resin is 0.48-0.54 eq / 100g and the molecular weight is 3000-5000; The inhibitor is hydroquinone and the photoinitiator is benzophenone; The preparation method of esterified modified vanillic acid is as follows: 10 g of polyvinyl alcohol is dissolved in 100 mL of dimethyl sulfoxide under stirring at 100 ° C, and then 10 g of vanillic acid and 3 g of dibutyltin dilaurate are added, and the reaction is carried out for 12 hours to obtain a mixed solution, and the mixed solution is poured into 200 mL of acetone for precipitation for 2 hours, and the precipitate is crushed and sieved to obtain a solid powder with a particle size of about 120 mesh, and then washed with 100 mL of acetone, and finally vacuum dried at 60 ° C to constant weight to obtain esterified modified vanillic acid.

[0026] A method for preparing ultraviolet light-cured epoxy acrylic resin comprises the following steps: adding bisphenol A epoxy resin, esterified modified vanillic acid, trimethylbenzyl ammonium chloride, an inhibitor and a photoinitiator into a reactor equipped with a thermometer, a reflux condenser and a dropping funnel according to the component ratio at 100°C, adding methacrylic acid dropwise after mixing evenly, and completing the dropping within 1 hour, heating to 110°C, keeping the temperature for 1 hour, measuring the acid value every 1 hour, and measuring the acid value until the acid value drops to 4-5 mg KOH / (mg·g -1 ), stop the reaction, cool naturally to 70°C, discharge the material and store in the dark.

[0027] Comparative Example 2 A UV-curable epoxy acrylic resin comprises the following raw materials in parts by weight: 85 parts of bisphenol A epoxy resin, 20 parts of methacrylic acid, 25 parts of vanillic acid, 1 part of trimethylbenzyl ammonium chloride, 0.2 parts of inhibitor, and 3 parts of photoinitiator; The epoxy value of bisphenol A epoxy resin is 0.48-0.54 eq / 100g and the molecular weight is 3000-5000; The inhibitor is hydroquinone and the photoinitiator is benzophenone; A method for preparing ultraviolet light-cured epoxy acrylic resin comprises the following steps: adding bisphenol A epoxy resin, vanillic acid, trimethylbenzyl ammonium chloride, an inhibitor and a photoinitiator into a reactor equipped with a thermometer, a reflux condenser and a dropping funnel according to the component ratio at 100°C, adding methacrylic acid dropwise after mixing evenly, and completing the dropping within 1 hour, heating to 110°C, keeping the temperature for 1 hour, measuring the acid value every 1 hour, and measuring the acid value until the acid value drops to 4-5 mg KOH / (mg·g -1 ), stop the reaction, cool naturally to 70°C, discharge the material and store in the dark.

[0028] The physical and chemical properties of the UV-curable epoxy acrylic resins prepared in Examples 1-3 and Comparative Examples 1-2 were tested. The testing method is as follows. The test results are shown in Tables 1 and 2 below.

[0029] (1) Appearance, water solubility and storage stability tests Take 10g of UV-curable epoxy acrylic resin sample in a beaker and observe its appearance. Add water at a rate of 1g each time and record the critical points at which the sample becomes translucent and milky after being water-based. When the sample becomes translucent, seal the beaker with plastic wrap and store it away from light. Take it out after 15 days, 30 days, and 60 days to observe its color change.

[0030] (2) Viscosity test The viscosity of the UV-curing epoxy acrylic resin sample was measured using a NDJ-5S rotational viscometer. At room temperature, 5 g of UV-curing epoxy acrylic resin was placed in a beaker, and the 2# rotor was selected at a speed of 30 RPM for testing. When the system was stable, the data were recorded in sequence.

[0031] (3) Curing rate UV-curing epoxy acrylic resin at energy 100mj / cm 2 The curing test was carried out under the following conditions, with each curing time being 30 seconds. The number of times the cured coating reached surface dryness was used to characterize its curing speed.

[0032] (4) Coating flatness UV-curable epoxy acrylic resin was evenly coated on the PMMA acrylic sheet with a coating area of ​​25 mm × 5 mm and a resin layer thickness of 1 mm. The sheet was placed on a horizontal sample table and heated at an energy of 100 mj / cm 2 After curing under the appropriate conditions, the flatness of the cured film was evaluated.

[0033] (5) Tensile strength Will be at 100mj / cm 2 The UV-cured epoxy acrylic resin cured under the conditions was cut into strips with a size of 20 mm × 5 mm × 5 mm, hung horizontally on an NLW tensile shear testing machine, stretched at both ends, and the tensile force F when the strip broke was recorded. The area S was calculated based on the width and thickness of the strip. The tensile strength was calculated as follows: tensile strength = F / S, where F is the pressure on the strip when it breaks, in N; S is the area of ​​the fracture surface of the strip, in mm 2 .

[0034] (6) Oxygen index value The oxygen index value will be 100mj / cm 2 UV-curable epoxy acrylic resin treated under O 2 and N 2 The minimum oxygen concentration required to maintain combustion in a mixed atmosphere is expressed as a volume percentage. According to the international standard ASTM D2863, the calculation formula is oxygen concentration % = oxygen flow rate / (oxygen flow rate + nitrogen flow rate) × 100%.

[0035] Table 1 Appearance, water solubility and storage stability test of UV-cured epoxy acrylic resin Table 2 Viscosity, contact angle, tensile strength, curing rate and oxygen index value test of UV-cured epoxy acrylic resin As can be seen from Table 1, the UV-curable epoxy acrylic resins prepared in Examples 1-3 have excellent storage stability, are still clear solutions after 60 days of storage, and are still colorless and transparent after drying, and have improved water solubility. They can be in liquid form when used, which is convenient to use. Comparative Example 2 uses unmodified vanillic acid, which has poor water solubility and storage stability. As can be seen from Table 2, the UV-curable epoxy acrylic resins prepared in Examples 1-3 have low viscosity, fast curing rate, excellent film smoothness, excellent mechanical properties and good flame retardant properties, which can meet the needs of actual production and life and have a wide range of applications. The UV-curable epoxy acrylic resins prepared in Comparative Examples 1 and 2 have low oxygen index values, poor flame retardant properties, and limited application areas. Compared with Comparative Example 2 (unmodified vanillic acid), the mechanical properties of the UV-curable epoxy acrylic resin prepared in Comparative Example 1 (polyvinyl alcohol-modified vanillic acid) are improved.

[0036] Although the embodiments of the present application have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present application, and that the scope of the present application is defined by the appended claims and their equivalents.

Claims

1. A UV-curable epoxy acrylic resin, characterized in that: The invention comprises the following raw materials in parts by weight: 80-90 parts of bisphenol A epoxy resin, 20-30 parts of methacrylic acid, 20-30 parts of modified vanillic acid, 0.1-3 parts of trimethylbenzyl ammonium chloride, 0.01-1 parts of inhibitor, and 1-6 parts of photoinitiator; the preparation method of the modified vanillic acid is as follows: Step S1, dissolving dicyandiamide, urea and polyvinyl alcohol in dimethylformamide at 100-140° C. in an inert atmosphere, adding phosphoric acid and mixing evenly, stirring for 1-3 hours to obtain a mixed solution, and purifying the mixed solution by ultrafiltration, precipitating and vacuum drying to obtain flame-retardant polyvinyl alcohol; Step S2, dissolving the flame-retardant polyvinyl alcohol obtained in step S1 in dimethyl sulfoxide at 120-140° C. with stirring, then adding vanillic acid and dibutyltin dilaurate, reacting for 12-16 hours to obtain a mixed solution, pouring the mixed solution into acetone for precipitation, washing the precipitate with acetone, then crushing, sieving, and vacuum drying to obtain modified vanillic acid.

2. The UV-curable epoxy acrylic resin according to claim 1, characterized in that: The bisphenol A epoxy resin has an epoxy value of 0.48-0.54 eq / 100g and a molecular weight of 3000-5000.

3. The UV-curable epoxy acrylic resin according to claim 1, characterized in that: The polymerization inhibitor is one or more of p-hydroxyanisole, hydroquinone, 2,5-dimethylresorcinol, 2,6-di-tert-butyl-p-cresol, and p-chloroanisole.

4. The UV-curable epoxy acrylic resin according to claim 1, characterized in that: The photoinitiator is one or more of 2,4-dihydroxybenzophenone, benzophenone, 1-hydroxycyclohexyl phenyl ketone and benzoin ethyl ether.

5. The UV-curable epoxy acrylic resin according to claim 1, characterized in that: The mass ratio of polyvinyl alcohol, dicyandiamide, urea and phosphoric acid in step S1 is 6:4-6:8-10:5-8, and the amount of polyvinyl alcohol added to the dimethylformamide is 6-12 g / 100 mL.

6. The UV-curable epoxy acrylic resin according to claim 1, characterized in that: The mass ratio of the flame retardant polyvinyl alcohol, vanillic acid and dibutyltin dilaurate in step S2 is 16:15-20:1-3, and the amount of the flame retardant polyvinyl alcohol added to the dimethyl sulfoxide is 8-16 g / 100 mL.

7. The method for preparing the UV-curable epoxy acrylic resin according to any one of claims 1 to 6, characterized in that: The following steps are involved: At 90-100°C, under stirring conditions, add bisphenol A epoxy resin, modified vanillic acid, trimethylbenzyl ammonium chloride, inhibitor and photoinitiator into a reactor equipped with a thermometer, a reflux condenser and a dropping funnel according to the component ratio, mix well and then drop methacrylic acid, and complete the dropwise addition within 0.5-1.5 hours, raise the temperature to 100-110°C, keep the temperature for 0.5-1.5 hours, measure the acid value every 1 hour, and wait until the acid value drops to 4-5 mg KOH / (mg·g -1 ), stop the reaction, cool naturally to 60-70°C, discharge the material and store in the dark.

8. Use of the UV-curable epoxy acrylic resin according to any one of claims 1 to 6 in wood floor paint, plastic paint, template coating or paper varnish.

Citation Information

Patent Citations

  • Special resin for water-based ultraviolet curing coating, and preparation method and application thereof

    CN103819654A

  • A UV-curable low-viscosity epoxy acrylate resin, its preparation method and application

    CN107163225B